Assessment of Risk Factors of Chronic Kidney Disease among Patients Attending Medical City Complex - Nabaa Wisam Sabri; Buthaina Ateyah Rashid; Raheem Saber Shwiehk; Azad H. Mahdy (Journal of Techniques)
Chronic kidney disease is a worldwide health problem that is defined as structural abnormalities or progressive or permanent loss of renal function for 3 months or more, which is usually associated with a decrease in glomerular filtration rate (GFR) of less than 60 mL/min/1.73 m2 or persistent proteinuria, which can lead to end-stage renal disease (ESRD) or kidney failure. To assess the risk factors leading to chronic kidney disease among the patients between cases and controls in the Medical City Complex. The study was conducted in hospitals of the medical city complex (Baghdad Teaching Hospital, Nursing Home Private Hospital, Ghazy Al-Hariri Hospital for Surgical Specialist, and kidney diseases and Transplant Center) in Baghdad, Iraq, and was designed as a case-control. There were 300 participants (150 cases and 150 controls). Data was collected over five months. The findings show that the highest percentage (20%) was within the age group 50–59 years old in the case study group, with a mean age of patients and controls of 47.71 ± 17.42 and 48.54 ± 17.43 years, respectively, and there were significant sociodemographic risk factors for CKD with gender and residency (p. value < 0.05). There was a significant link between medical history and the outcome of this investigation (p. value < 0.05 and OR > 1) All of the risk factors for CKD were hypertension, acute kidney disease, HCV infection, hyperlipidemia, renal stones, anemia, and cardiovascular disease. alcohol consumption had a significant difference with CKD (p. value =0.004). Increased intake of antihypertensive medical drugs also increases the risk of CKD (p. value =0.000). There is a significant association between patients' gender and residence, the patients with hypertension, AKI, HCV infection, hyperlipidemia, renal stones, anemia, and CVD had a significant relationship with CKD. The risk of CKD is increased in people who have had alcoholism and also in patients who have taken antihypertensive medication, The study recommends educating people about the risk factors of CKD, encouraging them to adopt a healthy diet, and healthy lifestyle, and encouraging alcohol cessation through special programs. The GFR test and other routine clinical tests must be performed regularly to monitor the change in kidney functions.